AuPt/3DOM CoCr2O4: Highly Active Catalysts for the Combustion of Methane - Xiyun Jiang; Yuxi Liu, Jiguang Deng; Xingtian Zhao; Shan Sun; Chengwei Zhai; Fei Peng; Hongxing Dai (The Global Environmental Engineers, 2017)
Three-dimensionally ordered macroporous (3DOM) CoCr2O4 and its supported bimetallic Auy Pt nanocatalysts (xAuyPt/3DOM CoCr2O4, x = 0.49, 0.98, and 1.92 wt%; Au/Pt molar ratio (y) = 0.99, 0.98, and 1.01) were prepared using the polymethyl methacrylate-templating and polyvinyl alcohol-protected reduction methods, respectively. Physicochemical properties of the samples were characterized by means of various techniques. Catalytic activities of the xAuyPt/3DOM CoCr2O4 samples were evaluated for methane combustion. It is found that the 3DOM CoCr2O4 support possessed a single-phase and cubic spinel-type crystal structure, the xAuyPt/3DOM CoCr2O4 samples displayed a high-quality 3DOM architecture and a surface area of 32-33 m2/g, and the AuyPt nanoparticles (NPs) with a size of 3-5 nm were well dispersed on the 3DOM CoCr2O4 surface. The loading of an appropriate amount of AuyPt NPs could enhance the adsorbed oxygen species concentration and low-temperature reducibility of the sample. Among all of the samples, 0.98Au0.98Pt/3DOM CoCr2O4 showed the best catalytic performance: the T10%, T50%, and T90% (temperatures required for achieving methane conversion of 10, 50, and 90 %, respectively) were 253, 315, and 354 oC at a space velocity of 20,000 mL/(g h). It is concluded that the good activity of 0.98Au0.98Pt/3DOM CoCr2O4 was associated with its highly dispersed Au0.98Pt NPs, high adsorbed oxygen species concentration, good low-temperature reducibility, and strong interaction between Au0.98Pt NPs and 3DOM CoCr2O4.